A Parametric Study of Confinement Effects to the Interaction Diagram of P-M for High-Strength Concrete Columns - Nur Fithriani Fatma Cholida; A Antonius; Faiqun Ni'am (Universitas Islam Sultan Agung, 2018)
In reinforced concrete columns design, P-M interaction diagram is used as axial load control and column bending without taking into account the effect of lateral reinforcement bars. Design principles that ignore the effect of reinforcement bars will result in low value of actual axial capacity of column. This paper presents the effect of lateral reinforcement with a case study of square-sectional columns on high-strength concrete. The equation of unconfined concrete strength enhancement is based on Mander, Legeron, Imran, Antonius and Muguruma models. The reviewed parameters include compressive strength of concrete, reinforcement configuration, and spacings of confinement. The result of the analysis is a comparison of P-M diagram based on confinement models. It shows that confinement significantly influences axial capacity of column, yet it has a certain collapse point at point P = 0 in all models. This is caused by longitudinal reinforcement system. Configuration of reinforcement, spacing and confinement models greatly affects the collapse behavior of column, whether the collapse is classified as compressive collapse or tensile collapse based on the P-M diagram.